High definition versus standard definition white light endoscopy for detecting dysplasia in patients with Barrett's esophagus. Issue 8 (10th September 2014) - Sami, S. S.; Subramanian, V.; Butt, W. M.; Bejkar, G.; Coleman, J.; Mannath, J.; Ragunath, K.
Summary: High‐definition endoscopy systems provide superior image resolution. The aim of this study was to assess the utility of high definition compared with standard definition endoscopy system for detecting dysplastic lesions in patients with Barrett's esophagus. A retrospective cohort study of patients with non‐dysplastic Barrett's esophagus undergoing routine surveillance was performed. Data were retrieved from the central hospital electronic database. Procedures performed for non‐surveillance indications, Barrett's esophagus Prague C0M1 classification with no specialized intestinal metaplasia on histology, patients diagnosed with any dysplasia or cancer on index endoscopy, and procedures using advanced imaging techniques were excluded. Logistic regression models were constructed to estimate adjusted odds ratios and 95% confidence intervals comparing outcomes with standard definition and high‐definition systems. The high definition was superior to standard definition system in targeted detection of all dysplastic lesions (odds ratio 3.27, 95% confidence interval 1.27–8.40) as well as overall dysplasia detected on both random and target biopsies (odds ratio 2.36, 95% confidence interval 1.50–3.72). More non‐dysplastic lesions were detected with the high‐definition system (odds ratio 1.16, 95% confidence interval 1.01–1.33). There was no difference between high definition and standard definition endoscopy in the overall (random and target) high‐grade dysplasia or cancers detected (odds ratio 0.93, 95% confidence interval 0.83–1.04). Trainee endoscopists, number of biopsies taken, and male sex were all significantly associated with a higher yield for dysplastic lesions. The use of the high‐definition endoscopy system is associated with better targeted detection of any dysplasia during routine Barrett's esophagus surveillance. However, high‐definition endoscopy cannot replace random biopsies at present time.